Stochastic Hydro‐Financial Watershed Modeling for Environmental Impact Bonds. Issue 8 (17th August 2020) - Brand, Matthew W.; Gudiño‐Elizondo, Napoleon; Allaire, Maura; Wright, Steven; Matson, Waylon; Saksa, Phil; Sanders, Brett F.
Abstract: Soil erosion, poor water quality, and degraded ecosystems impose major cost burdens and challenges for stormwater managers. We present a stochastic hydro‐financial watershed modeling framework for designing an Environmental Impact Bond (EIB)—a new form of financing for comprehensive, watershed scale interventions. EIBs provide capital for interventions that is repaid over time with interest by stakeholders who experience reduced costs (savings). The EIB is also structured so stakeholders and investors share the reward of cost savings. The framework estimates cost savings from interventions and accounts for aleatory and epistemic uncertainty in costs, which in turn impacts the financial terms of the EIB. In particular, we show a method to reward investors for taking on the risk that interventions fail. The framework is applied to a transnational pollution and sedimentation problem on the U.S.‐Mexico border and has broad applicability for a wide range of environmental problems. Plain Language Summary: Soil erosion, poor water quality, and degraded ecosystems pose significant management challenges. Oftentimes, the key issue is not a lack of understanding about what is needed to address these problems but the inability to finance solutions at the scale that is needed to be effective. Financial barriers may be cash flow limitations, political constraints, legal constraints, or other factors. Environmental impact bonds (EIBs) are a new form of financing capable of overcoming institutional and cash flow barriers: Investors provide the capital required for comprehensive watershed interventions, which is repaid over time with interest by stakeholders who experience a reduction in management costs or savings. This paper describes a modeling method for determining a fair interest rate and return period to reward investors for the risk that interventions fail. After presenting a formulation of the method, it is applied to a sediment management problem at the U.S.‐Mexico border and the feasibility of an EIB is for several possible interventions is shown. General strategies for making EIBs feasible are also reported. Key Points: A stochastic watershed modeling framework is developed to support the development of an environmental impact bond Bond period and interest rates are linked to distributions of costs that account for aleatory and epistemic uncertainty The feasibility of financing interventions to address watershed erosion problems at the U.S.‐Mexico border is shown